2017
DOI: 10.1080/13648470.2017.1317194
|View full text |Cite|
|
Sign up to set email alerts
|

Counting bodies? On future engagements with science studies in medical anthropology

Abstract: Thirty years ago, Nancy Scheper-Hughes and Margaret Lock outlined a strategy for 'future work in medical anthropology' that focused on three bodies. Their article -a zeitgeist for the fieldsought to intervene into the Cartesian dualisms characterizing ethnomedical anthropology at the time. Taking a descriptive and diagnostic approach, they defined 'the mindful body' as a domain of future anthropological inquiry and mapped three analytic concepts that could be used to study it: the individual/ phenomenological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…More specifically, this may mean an expansion of these 14 themes. Five of the original research articles that we found did not fit within these themes but suggested new, primarily qualitative themes: inter-and trans-disciplinary research development and directions (28,29), ecological behavior and spiritual healing (30)(31)(32) and participatory methods of communication. The need for an expansion of the themes was supported by the lack of congruence between the keywords provided by authors and the expert-derived themes used in our content analysis.…”
Section: Discussion Interpretationmentioning
confidence: 93%
“…More specifically, this may mean an expansion of these 14 themes. Five of the original research articles that we found did not fit within these themes but suggested new, primarily qualitative themes: inter-and trans-disciplinary research development and directions (28,29), ecological behavior and spiritual healing (30)(31)(32) and participatory methods of communication. The need for an expansion of the themes was supported by the lack of congruence between the keywords provided by authors and the expert-derived themes used in our content analysis.…”
Section: Discussion Interpretationmentioning
confidence: 93%
“…As Tim Rhodes and Kari Lancaster (2019) write, numbers are afforded life through their entanglements with situated practices, an important part of which is learning with measuring objects that become part of a way of knowing. Looking at making measuring bodies––not only measured bodies––attends to Yates-Doerr’s (2017) plea to engage with studying when, where, and with what effects embodiment matters. It adds insights into how counting gets embodied by medical practitioners as a way of knowing the world and in the crafting of their future patients.…”
Section: Measuring Tapes and The Inner Scaffoldmentioning
confidence: 99%
“…The households that I discuss in this paper were affected by multiple forms of malnourishment (Branca et al, 2019 ); under-nutrition, micronutrient deficiencies and anaemia were all present, affecting the health of household members at all stages of the lifecourse, and the younger women responsible for cooking shared meals and nourishing the family were confronted with the significant task of producing an adequate amount of food that met the needs of everyone in the household. This was further complicated by the fact that in Dakar, as Emily Yates-Doerr writes of households in Guatemala, women ‘did not cook for bodies, but for diffuse and shifting collectives’ (Yates-Doerr, 2017 , p. 143). In a context where all food is shared and the act of collective eating carries a strong moral weight and cultural significance, there is significant pressure for everyone to eat from the collective bowl and crafting an individual ‘diet’ is an extremely complex undertaking.…”
Section: Introductionmentioning
confidence: 99%